Energia mecânica, energia térmica e moagem na extrusão de alimentos para cães e gatos - Sá, Fabiano Cesar [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The efficiency of the extrusion process is directly related to the total energy transferred to the dough feed. Single screw extruders usually implement around 20kWh / ton of specific mechanical energy (SME), but less is known about the implementation of the specific thermal energy (STE) and the implications of the relationship between STE/SME processing of dog food and cats. This study evaluated the effects of the implementation of three relations between STE/SME on the macrostructure of estrusados, gelatinization, loss of nutrients, nutrient digestibility and palatability of food for dogs and cats. For each species, the experiment included a formulation processed in order to obtain three relations STE/SME totaling three diets for species. Nutrient digestibility was studied in 18 dogs or 18 cats, the total collection of feces. The palatability of the diets was compared for the two vessels method, at least 30 animals by comparison. The data were submitted to ANOVA and Tukey's test (P <0.05). Feed production was possible with different SME (8, 20 and 30 kWh / t) and relations STE/SME, but with total specific energy next. These had the same bulk density, gelatinization of starch and resistant starch. Provided to animals showed digestibility and similar energy production and resulted in similar characteristics of feces and does not alter the concentration of the fermentation product in the feces. There was, however, greater complexation fat as applied SME over the products (P <0.05). Dogs and cats had lower consumption of feed with 30 kWh / t, compared others (P <0.05). Dogs further preferred feed 20 over the 8 kWh / t (P <0.05), while for the latter cats had similar consumption. After extrusion was increasing content of some amino acids and an average reduction of 55% of its selenium content (P <0.05). It was concluded that different relations between SME and STE can be applied in the production of food for dogs and cats, with sufficient ...

A eficiência do processo de extrusão está diretamente relacionada à energia total transferida para a massa de ração. Extrusoras de rosca simples usualmente implementam ao redor de 20kWh/ton de energia mecânica específica (EME), mas menos se conhece à respeito da implementação de energia térmica específica (ETE) e das implicações da relação entre ETE:EME no processamento de alimentos para cães e gatos. O presente estudo avaliou os efeitos da implementação de três relações entre ETE:EME sobre a macroestrutura dos estrusados, gelatinização do amido, perda de nutrientes, digestibilidade dos nutrientes e palatabilidade de alimentos para cães e gatos. Para cada espécie, o experimento incluiu uma formulação processada de modo a se obter 3 relações ETE:EME, totalizando 3 dietas por espécie. A digestibilidade dos nutrientes foi estudada com 18 cães ou 18 gatos, pelo método de coleta total de fezes. A palatabilidade das dietas foi comparada pelo método de duas vasilhas, com no mínimo 30 animais por comparação. Os dados obtidos foram submetidos a análise de variância e comparados pelo teste de Tukey (P<0,05). Foi possível a produção de rações com diferentes EME (8, 20 e 30 kWh/t) e relações ETE:EME, mas com energia específica total próximas. Estas apresentaram mesma densidade aparente, gelatinização do amido e teor de amido resistente. Fornecidas aos animais, tiveram digestibilidade dos nutrientes e da energia semelhantes, resultaram em produção e características das fezes semelhantes e também não alteram a concentração de produtos da fermentação nas fezes. Houve, no entanto, maior complexação de gordura à medida que se aplicou mais EME nos produtos (P<0,05). Cães e gatos apresentaram menor consumo da ração com 30 kWh/t, em comparação às demais (P<0,05). Cães preferiram ainda a ração com 20 em detrimento da com 8 kWh/t (P<0,05), enquanto para gatos estas últimas tiveram consumo...
Keywords: Cão - Alimentação e rações; Gato - Alimentação e rações; Aminoacidos na nutrição animal; Digestão; Selenio na nutrição animal; Amino acids in nutrition